2013
DOI: 10.1371/journal.pone.0071665
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Multi-Deficiencies-Diet on Bone Parameters of Peripheral Bone in Ovariectomized Mature Rat

Abstract: Many postmenopausal women have vitamin D and calcium deficiency. Therefore, vitamin D and calcium supplementation is recommended for all patients with osteopenia and osteoporosis. We used an experimental rat model to test the hypothesis that induction of osteoporosis is more efficiently achieved in peripheral bone through combining ovariectomy with a unique multi-deficiencies diet (vitamin D depletion and deficient calcium, vitamin K and phosphorus). 14-week-old Sprague-Dawley rats served as controls to examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 62 publications
1
25
0
2
Order By: Relevance
“…The mild bone loss or sometimes non-significant differences between CMS and control groups may be due not only to the induction mechanism but also to the time of observation. El Khassawna et al (2013), for example, have shown that tibia BV/TV of ovariectomized rats fed with multideficient diet, assessed by microcomputed tomography, can achieve less than 10% after three months of induction. Feik et al (1997) showed that in humans, cortical area of cross-sections from femoral midshaft increases in both sexes until the 7 th decade and then it starts to decline, more pronounced in women.…”
Section: Discussionmentioning
confidence: 99%
“…The mild bone loss or sometimes non-significant differences between CMS and control groups may be due not only to the induction mechanism but also to the time of observation. El Khassawna et al (2013), for example, have shown that tibia BV/TV of ovariectomized rats fed with multideficient diet, assessed by microcomputed tomography, can achieve less than 10% after three months of induction. Feik et al (1997) showed that in humans, cortical area of cross-sections from femoral midshaft increases in both sexes until the 7 th decade and then it starts to decline, more pronounced in women.…”
Section: Discussionmentioning
confidence: 99%
“…The non-mineralised collagen matrix with small remains of Ca in the centre of the trabecular has been described in more detail in our previous study [11]. After histological and serological investigations El Khassawna et al also conclude the development of osteomalacia in this rat model [26]. In consequence the Ca quantification might become more complicated due to measurement of non-mineralised regions which might result in too low Ca values for the OVX and diet group.…”
Section: Resultsmentioning
confidence: 69%
“…Results were expressed in fold of amplification. Better description of methodology were scrutinized in the following references [18,19].…”
Section: Bone Expression Mrna Calbindin 28 Kda (Cbp28k)mentioning
confidence: 99%
“…As long as the effects of VK in bone metabolisms are still inconclusive, we decided to investigate its effects in a well-established model for osteoporosis, the ovariectomized (OVX) mice [17][18][19]. Surgical removal of the ovaries mimics menopause resulting in a suitable model to investigate mechanisms of VK action in bone as well as its interaction with estrogen either on BMD or microarchitecture [19].…”
Section: Introductionmentioning
confidence: 99%